2000
DOI: 10.1046/j.1365-2168.2000.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the functional outcome of restorative proctocolectomy in ulcerative colitis

Abstract: While preoperative data may help in selecting patients suitable for restorative proctocolectomy, prevention of late complications seems most important in improving the functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
2
23
3
Order By: Relevance
“…Seven percent of these patients had developed chronic pouchitis. Although pouchitis has been reported to contribute to pouch dysfunction, 17 in the present study, it did not. Other authors have also reported that in patients followed up for more than ten years, function may remain good despite occasional episodes of pouchitis.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Seven percent of these patients had developed chronic pouchitis. Although pouchitis has been reported to contribute to pouch dysfunction, 17 in the present study, it did not. Other authors have also reported that in patients followed up for more than ten years, function may remain good despite occasional episodes of pouchitis.…”
Section: Discussioncontrasting
confidence: 77%
“…Median follow-up for the 37 patients with J-pouches was nine (mean, 9.4 Ϯ 1.6, range, [8][9][10][11][12][13][14][15][16][17] years. Major daytime incontinence was unchanged in 89 percent and worse in 11 percent.…”
Section: Resultsmentioning
confidence: 99%
“…These data are in agreement with other reports 7,8 . Of the 3 deaths in the late follow-up, 2 patients died of cancer, 1 of which was colonic.…”
Section: Discussionsupporting
confidence: 83%
“…To what extent the presence of extraintestinal manifestations should influence the choice of surgical treatment is not clear. Further studies are required to address this issue 7 .…”
mentioning
confidence: 99%
“…Although this procedure is associated with low mortality, the postoperative morbidity caused by functional problems and complications is high. [3][4][5] In patients with UC, the most common long-term complication after IPAA is pouchitis. 4,[6][7][8][9] This acute, nonspecific, inflammatory condition of the ileal pouch can mimic inflammatory bowel disease.…”
mentioning
confidence: 99%